Chagas disease is a low health priority among high-risk Latin American migrants in Geneva, a qualitative study - Marina Gold; Yves Jackson; David Parrat (Elsevier, 2024)
This qualitative study of the situation of Latin American migrants with Chagas Disease in Geneva analyses how precarious migration-related socioeconomic conditions determine health priorities and disease perception. The study was conducted between 2016 and 2019 and is based on survey data collected in three Chagas-related community events, as well as on open-ended interviews with Bolivian migrants. This research contributes to more appropriate development of public health policies for migrants, as well as to a more nuanced and culturally sensitive understanding of how precarity affects the delivery of, and access to, healthcare in Western Europe. The significance of this research is to highlight how perceptions of Chagas Disease provide a lens to better understand the links between precarity and health among Bolivian migrants.